Estimation of IDF curves of extreme rainfall by simple scaling in Slovakia - BARA, Márta; KOHNOVÁ, Silvia; GAÁL, Ladislav; SZOLGAY, Ján; HLAVČOVÁ, Kamila (Contributions to Geophysics and Geodesy, 2009)
Scaling properties of the short term extreme rainfall has not been investigated so far in Slovakia. In this study the simple scaling theory is applied to the intensity- duration-frequency (IDF) characteristics of short duration rainfall. The rainfall data for the analysis consists of rainfall intensities of durations ranging from 5 minutes to 180 minutes and daily rainfall amounts for 55 stations from the whole territory of Slovakia, respectively, taken from the historical dataset of Šamaj and Valovič (1973) and from the database of the Slovak Hydrometeorological Institute (SHMI). The scaling behaviour of rainfall intensities was examined and it was shown that for time scaling, the statistical properties of rainfall follow the hypothesis of simple scaling. The scaling exponents were derived in all the analysed stations. In the selected test stations, the inﬂuence of excluding the 5 min duration on the derived IDF curves was also examined. The possibility of using wide sense simple scaling in Slovakia was demonstrated.